Adoption In Lucy Maud Montgomery's Novel Anne Of Green Gables (1908): A Psychoanalytic Approach - Prameswari, R. Sri Mey W; , Dr. Phil. Dewi Candraningrum, M.Ed (2016)
The major problem of this study is adoption. No every child can live with biological parents. The objective of this study is to analyze this novel based on the Psychoanalytic Approach. The writer employs qualitative method. The writer uses two data source: primary and secondary. The primary data source of this study is Anne of Green Gables novel by Lucy Maud Montgomery. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the research will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that adoption has big impacts in Anne Shirley life. Anne's adoption brings her to reach the goals in her life. Anne Shirley has extremely imagination in a lot of aspects of her life. Anne loves to be a teacher. She has many desires in her life. She tries hard to get what she wants. Anne does a lot of efforts and never gives up. Anne realizes without struggle her dreams will not come true.